Downsides to the empathic brain? A review of neural correlates of empathy in major depressive disorder - Choi, Dahna; Förster, Katharina; Alexander, Nina; Kanske, Philipp (Frontiers in Human Neuroscience, 2024)
Empathy as one of the basic prerequisites for successful social interactions seems to be aberrant in individuals with major depressive disorder (MDD). Although understanding empathic impairments in MDD is crucial considering the frequently reported social skill deficits in patients, the current state of research is still inconclusive, pointing to both elevated and impaired levels of empathy. In this review, we extend previous reports of MDD-related aberrations in self-reported and behavioral empathy by shedding light on the neural correlates of empathy in individuals with MDD. Study findings indicate a complex and potentially state-dependent association, comprising both elevated and lower neural activity in empathy-related brain regions such as the inferior frontal gyri, bilateral anterior insulae, and cingulate areas. Predominantly, lower activity in these areas seems to be induced by antidepressant treatment or remission, with accompanying behavioral results indicating a reduced negativity-bias in empathic processing compared to acute states of MDD. We propose a preliminary model of empathy development throughout the course of the disorder, comprising an initially elevated level of empathy and a somewhat detached and lower empathic responding during the further progression of the disorder or post-treatment. The seemingly multifaceted nature of the association between empathy and MDD requires further exploration in future multimodal and longitudinal studies. The study of neural correlates of empathy in MDD should prospectively be enlarged by including further socio-affective and -cognitive capacities in MDD and related mental disorders.